Origens do periodismo científico no Brasil - Freitas, Maria Helena de Almeida (2005)
It analyzes periodic publications of the area of sciences in Brazil in the beginning of 19th century, understanding them as one of them pillars of the institutionalization of science in the country. It more specifically evaluates O Patriota, Jornal Litterario, Politico, Mercantil &c. do Rio de Janeiro, first journal dedicated to the sciences and the arts in Brazil, published in 1813-1814, as also other journals that they had appeared until the decade of 1830, in order to evaluate the conditions of sprouting and the characteristics of these publications. The research also evaluates the scientific journals of the first scientific societies of 19th century in Brazil. It concludes that the brazilian periodic publications of first four decades of 19th century had only had conditions of survival and continuity when associates with scientific societies or institutions